Case Report Adrenal Myelolipoma (Journal of Surgical Sciences, 2019)
Adrenal myelolipoma is a rare tumor that is benign in nature, usually asymptomatic, unilateraland nonsecreting, With the widespread use of imaging modalities such as ultrasonographythe incidental detection of these tumors are increasing in frequency. We report acase of adrenal myelolipoma in a 45-year-old female who presented with pain in the rightupper abdomen, headache and hypertension. Myelolipoma as an incidental diagnosismight keep in mind and evaluate accordingly to validated protocol because of surgicalemergencies such as spontaneous retroperitoneal hemorrhage.Journal of Surgical Sciences (2016) Vol. 20 (2) :59-61